DIALOG KONSEP ALLAH: IMAN KRISTEN DAN KEPERCAYAAN LOKAL GEREJA ADAT MUSI - Haribulan, Christian Jinris Ricky (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Belief in a higher power is a religious experience that has existed since the beginning of human life. Humans began to formulate concepts related to powers beyond themselves. This study aims to examine the concept of God in the Christian faith and in the local beliefs of the Musi Traditional Church in Lirung District, Talaud Islands Regency. The focus of the research was directed at identifying similarities and differences in the understanding of God according to the two faith communities. The study was conducted in 2016 using a qualitative approach through observation, interviews, and documentation. The data obtained were analyzed inductively to discover patterns of meaning and understanding that are alive within the congregation. The results show that the congregation of the Musi Traditional Church understands God as the Father, the Creator, Jesus Christ as the Protector and Defender, and the Holy Spirit who dwells within the congregation members. This concept shows similarities with the Christian faith that emphasizes the Trinity, although colored by the local cultural context. This study recommends that the Christian church and the Musi Traditional Church strengthen congregation formation in understanding God so that faith can be deepened while still respecting local cultural identity. ABSTRAK Percaya kepada kuasa yang lebih tinggi merupakan pengalaman religius yang telah hadir sejak awal kehidupan manusia. Manusia mulai merumuskan mengenai konsep-konsep yang berkaitan dengan kuasa yang ada di luar dirinya. Penelitian ini bertujuan menelaah konsep Allah dalam iman Kristen dan dalam kepercayaan lokal Gereja Adat Musi di Kecamatan Lirung, Kabupaten Kepulauan Talaud. Fokus penelitian diarahkan untuk mengidentifikasi kesamaan dan perbedaan pemahaman Allah menurut kedua komunitas iman tersebut. Penelitian dilakukan pada tahun 2016 dengan pendekatan kualitatif melalui observasi, wawancara, dan dokumentasi. Data yang diperoleh dianalisis secara induktif untuk menemukan pola makna dan pemahaman yang hidup dalam jemaat. Hasil penelitian menunjukkan bahwa jemaat Gereja Adat Musi memahami Allah sebagai Bapa Pencipta, Yesus Kristus sebagai Pelindung dan Pembela, serta Roh Kudus yang diam dalam diri anggota jemaat. Konsep ini memperlihatkan kemiripan dengan iman Kristen yang menekankan Tritunggal, walaupun diwarnai konteks budaya lokal. Penelitian ini merekomendasikan agar gereja Kristen dan Gereja Adat Musi memperkuat pembinaan jemaat dalam pemahaman Allah sehingga iman dapat diperdalam sekaligus tetap menghargai identitas budaya lokal.